Analysis of output power smoothing method of the solar chimney power generating system. (13th December 2012) - Ming, Tingzhen; Meng, Fanlong; Liu, Wei; Pan, Yuan; Kiesgen de Richter, Renaud
SUMMARY Severe fluctuation of the output power is a common problem in the generating systems of various renewable energies. The concept of output power fluctuation factor of renewable energy power generating systems was put forward in this paper. Aiming to decrease the fluctuation factor of output power in solar chimney power generating systems (SC), a novel hybrid energy storage system made of water, and sandstone was employed to replace the traditional sandstone energy storage system. The mathematical models of fluid flow, heat transfer and power generating features of SC were established and the influences of material, depth, areas and location of the energy storage layer upon output power were analyzed. The simulation results indicated that adopting the hybrid energy storage of water and sandstone can effectively decrease the fluctuation factor of SC output power and hence smooth the SC output power. In addition, according to the largest daily power generating capability or the smallest peak fluctuation factor, the corresponding optimum depth of the water energy storage layer would be 5 cm or 20 cm, respectively. Copyright © 2012 John Wiley & Sons, Ltd.